Penerapan Manajemen Mutu dalam Meningkatkan Prestasi Akademik di MI Al Azhar Tahun Pelajaran 2019/2020 - Rohman, Muhammad Rofiqur; Qosim, Achmad; Khoeron, Khoeron (STAI Denpasar Bali, 2022)
Quality management is a means that allows it to be used as a basis for improving the education system. One of the problems faced by MI Al Azhar Tuban is the decline in student academic achievement recently. So that it has an impact on the management of madrasah management. However, this problem can still be resolved through quality management which is implemented in Madrasah Ibtida'iyah. The applied management standards must be based on the National Education System. One of the successes of quality management in improving academic achievement is the increasing quality of student learning. Therefore the application of quality management is very important and helpful for educational institutions that have decreased student academic achievement in order to achieve graduates who are superior in the field of academic achievement. The focus of research in this study is (1) How is the application of quality management in improving academic achievement at MI Al Azhar Tuban Badung? (2) What are the supporting and inhibiting factors in the implementation of Quality Management at MI Al Azhar Tuban Badung? The research objectives in this thesis are (1) To determine how the application of quality management in improving academic achievement at MI Al Azhar Tuban Badung (2) To determine the supporting and inhibiting factors of the implementation of quality management at MI Al Azhar Tuban Badung. The type of research used is descriptive qualitative research at Madrasah Ibtida'iyah Al Azhar Tuban Badung with data collection techniques in this study include: observation, interviews, documentation, while the data validity test was carried out by triangulation techniques, as long as the research was analyzed with data reduction steps. presentation of data, and drawing conclusions. In this thesis results: (1) the application of quality management in improving academic achievement includes quality planning, quality improvement, quality control and quality assurance (2) The factors that support and hinder the implementation of quality management are internal and external factors.